Mental Health Awareness from the School Level: A Critical Review of Mindfulness Practices and Short Therapeutic Activities for Student Well-Being - Magar, Sandesh Sinjali (Research Journal in Psychology and Behavioral Studies, 2026)
The mental health problems of children and young people are now a major public health and educational issue across the world, and there has been a rise in the incidence of anxiety, depression, stress, emotional dysregulation and behavior problems in relation to academic achievement and overall well-being. Early mental health promotion is important in school because the school is the setting which sensitises students during a time when their cognitive, emotional and social development is still at a crucial stage. This critical review looks at mental health awareness programs that are taught at the school level, focusing on mindfulness programs and brief therapeutic activities as effective, evidence-based tools to help students thrive. The review, based on current empirical research, systematic reviews, and international policies, synthesizes evidence on the effectiveness of school-based mental health education, mindful breathing, guided relaxation, gratitude practices, emotional check-ins, reflective journaling, as well as a suite of other brief therapeutic practices that can be integrated into regular classroom activities without interference with academic learning. The results suggest that early mental health awareness training can positively impact emotional skills, resilience, attention, self-awareness, social connection, and classroom engagement and decrease emotional stress, anxiety, and emotional distress. Five to fifteen minute time blocks of activities that have a therapeutic focus can be scientifically proven to have a positive effect on concentration, emotional stability, and positive learning settings, if delivered regularly by trained professionals. The review also highlights key implementation issues, such as insufficient training of teachers, mental health resources, cultural stigma, less access to policy support, and inequities in access across various learning environments. It highlights the need for the integration of mental health literacy in the school curriculum, increasing the cooperation between school educators, families, health services, and policy makers, and the implementation of culturally responsive and evidence-based interventions. In conclusion, the study suggests that integrating mental health promotion, mindfulness, and short therapeutic activities into the school's routine is a proactive and sustainable approach that can enhance the psychological well-being of students throughout their lives and contribute to a healthier school environment, thereby supporting their academic and personal growth.